Efficient Liquid‐Assisted Grinding Selective Aqueous Oxidation of Sulfides Using Supported Heteropolyacid Catalysts. Issue 10 (18th April 2019) - Trombettoni, Valeria; Franco, Ana; Sathicq, A. Gabriel; Len, Christophe; Romanelli, Gustavo P.; Vaccaro, Luigi; Luque, Rafael
Abstract: The present work reports the preparation of 40MoAl200 and its full characterization using a number of analytical techniques (XRD, TEM, TGA, BET, EDX). Liquid‐assisted ball milling proved to be a key tool to achieve both the best efficiency of 40MoAl200 as a novel Keggin type catalyst in the selective sulfoxidation reaction and also for succeeding in its effective recovery and reuse. In addition, the liquid assisted grinding process was studied in detail evaluating the influence of different parameters such as frequency of rotation (rpm), number and size of the stainless steel balls used and reaction time. The use of aqueous hydrogen peroxide is essential as water proved to exert a crucial role to improve both yields and selectivity towards sulfoxide formation. The procedure was representatively extended to a number of substrates with the possibility to extend the scope of the system to produce sulfoxides in high yields (up to 95 %) and satisfactory selectivities (up to 80 %). The catalyst proved to be recoverable and reusable under the optimized reaction conditions. Abstract : Mechanochemical green power ! Herein we report a ball milling sulfoxidation protocol using aqueous hydrogen peroxide solution as oxidant and 40MoAl200 as a novel Keggin type catalyst. Optimum reaction conditions were extended to other substrates producing sulfoxides in high yields (up to 95 %) and selectivity (up to 80 %).